Decreased Frequencies of Gamma/Delta T Cells Expressing Th1/Th17 Cytokine, Cytotoxic, and Immune Markers in Latent Tuberculosis-Diabetes/Pre-Diabetes Comorbidity - Kathamuthu, Gokul Raj; Kumar, Nathella Pavan; Moideen, Kadar; Menon, Pradeep A.; Babu, Subash (Frontiers in Cellular and Infection Microbiology, 2021)
Antigen-specific gamma-delta (γδ) T cells are important in exhibiting anti-mycobacterial immunity, but, their role in latent tuberculosis (LTB) with diabetes mellitus (DM) or pre-DM (PDM) and non-DM comorbidities have not been studied. Thus, we have studied the baseline, mycobacterial (PPD, WCL) and positive control antigen-stimulated  T cells expressing Th1 (IFN, TNF, IL-2) and Th17 (IL-17A, IL-17F, IL-22) cytokines, cytotoxic (perforin [PFN], granzyme [GZE B], granulysin [GNLSN]) and immune (GMCSF, PD-1, CD69) markers in LTB (DM, PDM, NDM) comorbidities by flow cytometry. In the unstimulated (UNS) condition, we did not observe any significant difference in the frequencies of  T cells expressing Th1, Th17 cytokines, cytotoxic and immune markers. In contrast, upon PPD antigen stimulation, the frequencies of  T cells expressing Th1 (IFN, TNF), Th17 (IL-17F, IL-22) cytokines, cytotoxic (PFN, GZE B, GNLSN) and immune (CD69) markers were significantly diminished in LTB DM and/or PDM individuals compared to LTB NDM individuals. Similarly, upon WCL antigen stimulation, the frequencies of  T cells expressing Th1 (TNF), Th17 (IL-17A, IL-22) cytokines, cytotoxic (PFN) and immune (PD-1, CD69) markers were significantly diminished in LTB DM and/or PDM individuals compared to LTB NDM individuals. Finally, upon P/I stimulation we did not observe any significant difference in the  T cell frequencies expressing cytokines, cytotoxic and immune markers between the study population. The culture supernatant levels of IFN, TNF and IL-17A cytokines were significantly increased in LTB DM and PDM after stimulation with Mtb antigens compared to LTB NDM individuals. Therefore, diminished  T cells expressing cytokines, cytotoxic and other immune markers and elevated levels of cytokines in the supernatants is a characteristic feature of LTB PDM/DM co-morbidities.